COMPARING INDIAN AND WESTERN RESPONSES TO PANDEMICS: EXISTENTIAL CRISES IN REBATI, A LIFE MISSPENT, AND TWILIGHT IN DELHI - Deepak; Kumar, Sanjiv (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This paper explores the existential themes in Indian and Western pandemic narratives, focusing on how pandemics are depicted in literature and their impact on human experience. Through a comparative analysis of works such as Rebati by Fakir Mohan Senapati, A Life Misspent by Suryakant Tripathi Nirala, and Twilight in Delhi by Ahmed Ali, alongside Western texts like The Plague by Albert Camus, The Last Man by Mary Shelley, and Love in the Time of Cholera by Gabriel García Márquez, this study examines how pandemics serve as catalysts for existential crises and reflections on mortality, love, and human connection. In Indian narratives, pandemics often highlight social decay, personal suffering, and the impact of colonialism, while Western narratives engage more directly with existentialism, absurdism, and resistance. In García Márquez’s novel, love becomes an existential response to death, providing meaning amidst suffering. By contrasting these narratives, this paper demonstrates that while pandemics bring death and despair, they also offer profound reflections on life’s meaning. The study shows how different cultural contexts shape literary responses to disease, illustrating both shared human concerns and distinctive cultural interpretations of suffering, mortality, and the quest for meaning. Ultimately, this comparative study offers new insights into the role of pandemics in shaping existential thought.